2016
DOI: 10.19044/esj.2016.v12n18p327
|View full text |Cite
|
Sign up to set email alerts
|

Fathers And Breastfeeding Process: Determining Their Role And Attitudes

Abstract: Breastfeeding is a vital for infants during their early stage of life and it is considered that fathers have an important role to make this process succeed; this study was done to determine father’s attitudes and involvement in the breastfeeding process. A study survey instrument designed to measure father’s attitudes regarding breastfeeding process, the degree of their involvement and fathers` surrounded cultural effect on their involvement. Instrument were piloted with 22 fathers who met the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
1
11
0
7
Order By: Relevance
“…Fathers in several studies reported concerns about the perceived insufficiency of breast milk (Brown & Davies, 2014) and the inconvenience when compared with infant formula (Henderson et al, 2011; Mitchell-Box & Braun, 2012), and viewed it as challenging for their breastfeeding partners (Abu-Abbas et al, 2016; Brown & Davies, 2014). In a cross-sectional postal survey in Ireland, most participants ( N = 417; 77.7%) responded with at least one disadvantage of breastfeeding (Bennett et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fathers in several studies reported concerns about the perceived insufficiency of breast milk (Brown & Davies, 2014) and the inconvenience when compared with infant formula (Henderson et al, 2011; Mitchell-Box & Braun, 2012), and viewed it as challenging for their breastfeeding partners (Abu-Abbas et al, 2016; Brown & Davies, 2014). In a cross-sectional postal survey in Ireland, most participants ( N = 417; 77.7%) responded with at least one disadvantage of breastfeeding (Bennett et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Cultural implications influenced fathers’ views of breastfeeding in public. For example, Abu-Abbas et al (2016) attributed Jordanian fathers’ consistent negative attitudes toward public breastfeeding to that country’s conservative cultural norms. In contrast, fathers who grew up in jurisdictions where exposure to breastfeeding was commonplace and normed felt comfortable with women breastfeeding in public (Mitchell-Box & Braun, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as income, educational level, paternity leave, antenatal classes’ attendance, and knowledge and attitudes regarding breastfeeding were found to influence fathers’ breastfeeding involvement. Culture plays an important role in influencing breastfeeding involvement among fathers (Abu-abbass, Kallash, & Shelash, 2016; Datta, Graham, & Wellings, 2012; Sherriff, Hall, & Panton, 2014). Our study aimed to bridge a gap by examining all of the identified independent factors that influenced fathers’ involvement in their partners’ breastfeeding found in the literature, and conducting our study in an Asian context (Singapore), bringing in central aspects of Asian patriarchal culture.…”
Section: Introductionmentioning
confidence: 99%
“…A high percentage of fathers interviewed declared to be in favor of breastfeeding in public, a possible sign of the changing times. Breastfeeding in public is still a controversial issue [33]: several studies have reported how it is often perceived by men as uncomfortable, embarrassing and even distasteful [18,21,34,35], showing a correlation with socio-economic status [18,35] and cultural background [30,36]. A significant push toward the rethinking of breastfeeding in public has been given by the implementation of the Baby-Friendly Community Initiative (BFCI) [9].…”
Section: Discussionmentioning
confidence: 99%